Religious Value in Nyadran Ceremony in Ngepringan Village, Sragen - Yuliningsih, Yuliningsih; Saddhono, Kundharu; Setiawan, Budhi (el Harakah: Jurnal Budaya Islam, 2018)
The struggle for modernity gave rise to the degradation of the value of character education. At this stage the revitalization of the value of religious local wisdom in tradition needs to be developed again. The existence of nyadran tradition in Ngepringan continues to be developed by mixing the value of local wisdom with religious values. This unique combination is a form of local wisdom against the individual culture that developed in the community, the development of modernity. This means that the community can not only uphold the cultural values of the ancestors, and also cannot adapt the tradition to conditions, and still insert religious values in it. Nyadran tradition is still played by the Ngepringan community because they are spiritual tourism and become a harmonizer political, social, economic and spiritual life. The collection of data information is through observation and interview with the Ngepringan village community. The purpose of this study is to explore religious values in the Nyadran ceremony procession. This type of research is ethnography with qualitative descriptive method. Data collection techniques use techniques, interviews, documentation, and language content. The data analysis uses interactive analysis technique. The results of this study are to reveal and describe the religious values in the ceremony procession that need to be preserved and improved by the Ngepringan village community in the face of modernity. Pergulatan modernitas melahirkan degradasi nilai pendidikan karakter. Pada titik ini revitalisasi nilai kearifan lokal religius dalam tradisi perlu dikembangkan kembali. Eksistensi tradisi nyadran di Ngepringan terus dikembangkan dengan mencampur nilai kearifan lokal dengan nilai religius. Perpaduan yang unik ini merupakan bentuk kearifan lokal melawan budaya individualis yang berkembang di masyarakat mengikuti perkembangan modernitas. Hal ini bermakna bahwa masyarakat disana tidak hanya menjunjung nilai-nilai budaya dari para leluhur, melainkan juga mampu menyesuaikan tradisi dengan kondisi, serta masih menyisipkan nilai-nilai religius di dalamnya. Tradisi nyadran masih tetap dipertahankan oleh masyarakat Ngepringan dikarenakan nyadran sebagai wisata rohani serta menjadi penyelaras kehidupan politik, sosial, ekonomi, dan agama. Informasi data diperoleh melalui observasi dan wawancara dengan masyarakat desa Ngepringan. Tujuan studi ini untuk menggali nilai religius dalam prosesi upacara nyadran. Jenis penelitian ini adalah etnografi dengan metode deskriptif kualitatif. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dokumentasi, dan analisis isi. Teknik analisis data yang digunakan adalah analisis interaktif. Hasil dari penelitian ini adalah mengungkap dan mendeskripsikan nilai religius dalam prosesi upacara nyadran yang perlu terus dilestarikan dan ditingkatkan oleh masyarakat desa Ngepringan dalam menghadapi modernitas.